2014
DOI: 10.3892/ijo.2014.2426
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fucodian on senescence are controlled by the p16INK4a-pRb and p14Arf-p53 pathways in hepatocellular carcinoma and hepatic cell lines

Abstract: Fucoidan is known to have various pharmacological effects, including antitumor activity. Although it has potential as a therapeutic agent for cancer cells, the anti-senescence effects and detailed mechanism of action remain poorly understood in normal hepatic cells. We investigated the anticancer functions of fucoidan using HepG2 cells as well as the mechanisms mediating the anti-senescent actions in Chang liver cells. Fucoidan effectively inhibited HepG2 cell viability and induced apoptosis. Also, fucoidan-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…In our study, we found that fucoidan treatment increases the proportions of lung cancer cells in G1 phases and the results are comparable to those of another reports3637. Several transducing signal pathways involved in fucoidan-mediated cell cycle arrest have been proposed, such as fucoidan activation of the AKT signaling pathway36 and activation of p16INK4a-Rb and p14Arf-p53 pathways37.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we found that fucoidan treatment increases the proportions of lung cancer cells in G1 phases and the results are comparable to those of another reports3637. Several transducing signal pathways involved in fucoidan-mediated cell cycle arrest have been proposed, such as fucoidan activation of the AKT signaling pathway36 and activation of p16INK4a-Rb and p14Arf-p53 pathways37.…”
Section: Discussionsupporting
confidence: 90%
“…These stressors also trigger DNA damage (cellular responses to such damages are regulated by either ATM-Chk2 or ATR-Chk1 pathways) and transactivate p53 and p21 CIP1 . Moreover, p21 CIP1 protein levels may lead to the inhibition of Cdk4/6 activity, which contribute to the G1 arrest or senescence [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we showed that fucoidan suppressed proliferation, but not apoptosis, in HLF cells. In contrast, previous studies reported that fucoidan induces apoptosis in several human HCC cell lines, including HepG2, Huh7 and SMMC-7721 cells (9,11,13,14). It is unclear why fucoidan did not induce apoptosis in HLF cells; however, one possibility is that there are different phenotypes between HCC cell lines.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, fucoidan exerts anticancer activity and is reported to inhibit the proliferation of colon, breast and prostate cancer cell lines (6)(7)(8). Although fucoidan suppresses HCC proliferation, most of the cell lines used in previous studies, including HepG2 and Huh-7 cells, were well-differentiated (9)(10)(11)(12)(13)(14). Thus, the anticancer activity of fucoidan against poorly differentiated HCC cells, such as the HLF cell line, remains unclear.…”
Section: Introductionmentioning
confidence: 99%